(untitled) - Mudassir Iqbal, Haroon Iqbal, Ahmad Ullah, Sara Nawaz (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This article is about the long-lasting impacts of Socio-economic crises on the indigenous culture of Pakistan through the analytical elucidation of the contemporary novel Moth Smoke by Mohsin Hamid. Moth Smoke is set in a Pakistani context and its story depicts the portrayal of Pakistan in 1998. This study aims to extricate and analyze the impacts of Socio-economic crises and problems developed from these crises by analyzing different characters and their distinct Socio-economic status along with their approach towards corruption. These crises are borne by income, education, occupation, health, and political participation in society. Basically, these factors establish a society, but if misused, then these are enough to deteriorate a society. Furthermore, it seeks to assess how the deterioration of the 1990s is still present in Pakistani society today. This research also attempts to show that it is vividly hard to find sovereignty, peace of mind and freedom as well as freedom of speech and the consequences or penalties of all the crises faced by Pakistan then and now.